2016
DOI: 10.1128/jvi.00177-16
|View full text |Cite|
|
Sign up to set email alerts
|

The Large Marseillevirus Explores Different Entry Pathways by Forming Giant Infectious Vesicles

Abstract: Triggering the amoebal phagocytosis process is a sine qua non condition for most giant viruses to initiate their replication cycle and consequently to promote their progeny formation. It is well known that the amoebal phagocytosis process requires the recognition of particles of >500 nm, and most amoebal giant viruses meet this requirement, such as mimivirus, pandoravirus, pithovirus, and mollivirus. However, in the context of the discovery of amoebal giant viruses in the last decade, Marseillevirus marseillev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 24 publications
7
94
0
Order By: Relevance
“…revealed that it was larger than the amoeba cell nucleus, in many cases occupying 1/3 of the amoeba cytoplasm (Fig. 1C, 2, S3, Table S4 and S5), as observed for other Marseilleviridae members (5, 8). …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…revealed that it was larger than the amoeba cell nucleus, in many cases occupying 1/3 of the amoeba cytoplasm (Fig. 1C, 2, S3, Table S4 and S5), as observed for other Marseilleviridae members (5, 8). …”
Section: Resultssupporting
confidence: 58%
“…Tokyovirus infection was accompanied by the large-scale development of VF in the amoeba cytoplasm, similar to that observed with other Marseilleviridae members (8, 10). A recent study reported that Marseillevirus possesses unique mechanisms for entry into Acanthamoeba cells, forming giant infectious vesicles surrounded by membranes, which differs from the entry mechanisms of other giant viruses (5). Tokyovirus was also found to display several morphological types in Acanthamoeba cells, such as giant vesicles including many viral particles surrounded by membranes and single particles in the amoeba cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed even smaller vesicles like exosomes (∼100 nm) may have the capacity to fit multiple HAV or HEV particles. This phenomena may not be limited to just RNA viruses as vesicular trafficking of viral populations has also been recently reported for Marseille virus, a large DNA virus of capsid size ∼250 nm, that appears to travel in populations of thousands within giant micrometer size vesicles [32]. …”
Section: Vesicles Enable High Multiplicity Of Infection and Can Facilmentioning
confidence: 62%
“…Even smaller vesicles, such as exosomes which are typically ~100nm in diameter, have the capacity to traffic multiple HAV or HEV viral particles [63]. While this novel type of viral transmission was first reported with (+) ssRNA viruses [3], recently a giant DNA virus, Marseille virus, has been discovered to also traffic between cells within micrometer vesicles, with each vesicle carrying hundreds of viral particles at once [95]. …”
Section: En Masse Viral Transmission and Increased Infection Efficienmentioning
confidence: 99%